Public Perceptions of the Emerging Human Monkeypox Disease and Vaccination in Riyadh, Saudi Arabia: A Cross-Sectional Study - Sultan Ayoub Meo; Thamir Al-Khlaiwi; Ziyad Fahad Aljofan; Aued Iaed Alanazi; Anusha Sultan Meo (Vaccines, 2022)
The human monkeypox disease is caused by the monkeypox virus (MPXV), which is a zoonotic disease. In the year 2022, the prevalence of monkeypox cases swiftly increased worldwide and the disease has now been declared a global public health emergency. The present study aimed to assess the public’s perceptions and knowledge of and attitudes toward monkeypox in Riyadh, Saudi Arabia. This questionnaire-based cross-sectional study was conducted from 15 May to 15 July 2022. The participants’ perceptions, knowledge, and attitudes were collected via a 28-item-based questionnaire survey. The survey was based on 1020 participants (554 (54.3%) were females, and 466 (45.7%) were males). The results reveal that out of 1020 participants, 799 (78.3%) respondents believed that monkeypox disease has developed into a pandemic situation, and 798 (78.2%) suggested that the disease is most common in Western and Central Africa. Further analysis shows that 692 (67.8%) respondents agreed that monkeypox cases are increasing worldwide, 798 (21.8%) believed that monkeypox is commonly transmitted through direct contact, and 545 (53.4%) of respondents reported that it is easily transmitted from human to human. Moreover, 693 (67.9%) participants mentioned that monkeypox disease is spreading more widely as people travel from one country to another, while 807 (79.1%) participants were aware that smallpox and monkeypox have similar clinical features. Furthermore, the majority of participants (p = 0.033) agreed that health officials should start a vaccination campaign to combat monkeypox. Regarding preventive measures and vaccination campaigns, 641 (62.8%) participants suggested that health officials should take public preventive measures and 446 (43.7%) recommended that health officials start vaccination campaigns against monkeypox. The knowledge of human monkeypox among the general population in Riyadh, Saudi Arabia was satisfactory for all ages, genders, levels of education, and economic groups. Moreover, the majority of participants proposed adopting preventive measures and starting a vaccination campaign to combat monkeypox disease. The knowledge of monkeypox in the public domain is a key factor to improve the public‘s capacity to minimize the disease burden and fight against viral infectious diseases at regional and global levels.